Ultrafast dynamics of subwavelength periodic ripples induced by single femtosecond pulse: from noble to common metals. (14th May 2020) - Cheng, Ke; Cao, Kaiqiang; Zhang, Yuchan; Han, Ruozhong; Feng, Donghai; Liu, Jukun; Zhang, Shian; Sun, Zhenrong; Jia, Tianqing
Abstract: The electron energy band structures and optical properties of silver and nickel are notably different, and they are identified as representative of noble and common metals, respectively. The ultrafast dynamics of the formation of periodic ripples on the surface of silver and nickel films induced by a single 800 nm, 50 fs laser pulse was investigated using the collinear pump-probe imaging method. The dependence of the transient ripple periods on the laser fluences was also studied. A surface plasmon polariton (SPP) model was developed to explain the formation of periodic ripples on noble and common metals induced by a femtosecond laser pulse. The evolution of the electron and the lattice temperature was investigated by numerically solving the equations of the two-temperature model. In addition, the effects of electron collision, localization of hot electrons, and inter-band transition on the dielectric constant in the excited states are discussed in detail as functions of laser fluence. The ripple periods obtained using the developed SPP model agree well with the experimental results, which supports the view that the SPP excitation plays an important role in the formation of periodic ripples. This model is expected to be a general approach for understanding the formation of subwavelength periodic ripples on metals induced by a femtosecond laser pulse.